1980
DOI: 10.1037/h0077662
|View full text |Cite
|
Sign up to set email alerts
|

Plasma corticosterone elevations in rats in response to consumption of concentrated sugar solutions.

Abstract: The results of three experiments indicated that male hooded rats exhibit marked corticosterone elevations when they freely consume .740 mol/1 (23.2% w/w) sucrose in tap water while nondeprived or .298 mol/1 (9.8% w/w) sucrose when deprived of water for 36 hr. The magnitude of the corticosterone elevation was increased by lengthening the duration of prior water deprivation (2, 24, or 48 hr) and by raising the sucrose solution concentration (.189, .298, or .470 mol/1). Free ingestion of tap water following sucro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Although the decrease was not to basal levels, there was no significant difference between the corticosterone level when water was available and that of the isotonic saline condition, an effect indicating that normal animals drank a sufficient amount of water to reduce the stress induced by the hydrational challenge. This is consistent with the results found by Hart, Coover, Shnerson, and Smotherman (1980) that cellular dehydration caused by sucrose consumption raised corticosterone levels and that the subsequent ingestion of water accelerated the decline of corticosterone concentrations from peak levels. Grossman (1975, 1976) reported that animals with selective lesions of the zona incerta, which is often destroyed during placement of LH lesions, display regulatory deficits in response to hypertonic saline and 2-deoxy-Dglucose, but not in response to polyethylene glycol or insulin.…”
Section: Discussionsupporting
confidence: 93%
“…Although the decrease was not to basal levels, there was no significant difference between the corticosterone level when water was available and that of the isotonic saline condition, an effect indicating that normal animals drank a sufficient amount of water to reduce the stress induced by the hydrational challenge. This is consistent with the results found by Hart, Coover, Shnerson, and Smotherman (1980) that cellular dehydration caused by sucrose consumption raised corticosterone levels and that the subsequent ingestion of water accelerated the decline of corticosterone concentrations from peak levels. Grossman (1975, 1976) reported that animals with selective lesions of the zona incerta, which is often destroyed during placement of LH lesions, display regulatory deficits in response to hypertonic saline and 2-deoxy-Dglucose, but not in response to polyethylene glycol or insulin.…”
Section: Discussionsupporting
confidence: 93%
“…This effect might be a regulatory mechanism to prevent even higher levels of circulating glucose resulting from corticosteroneinduced glycogenolysis or gluconeogenesis. In contrast, some rodent studies have reported that sucrose or fructose increases circulating corticosterone (Hart et al 1980, Gaysinskaya et al 2011, Choi et al 2017. However, these studies examined the effects of acute or short-term sucrose consumption and all focused on male rodents.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…The pituitary adrenal system is a highly sensitive index of environmental change (Hennessy & Lcvine 1979) and is activated by a broad range of stimuli (Hart, Coover, Shnerson & Smotherman 1980;Coover, Satterfield, Smotherman, Steinkc & Dorsa 1983). Goldman, Coover, and Levine (1973) have demonstrated, however, that this system is capable of bidirectional shifts.…”
Section: Pituitary-adrenal System Involvement In Conditioned Immune Cmentioning
confidence: 99%